Multidisciplinary treatment of a severe facial asymmetry - Atik Ezgi; Konas Ersoy; Kocadereli Ilken (Sciendo, 2018)
This case report presents the multidisciplinary treatment of an adult female who presented with a previously repaired right unilateral cleft lip and palate. The patient had been referred with a complaint of facial asymmetry, eating difficulties and a missing right central incisor. A clinical evaluation revealed severe facial asymmetry created by a mandibular deviation to the right side and a compensatory transverse cant of the maxillary occlusal plane. After pre-surgical orthodontic treatment, a Le Fort I osteotomy and a bilateral sagittal split osteotomy were performed. During post-surgical orthodontic treatment and, as a result of the rotational surgery, the maxillary left central incisor became the right central incisor. The left lateral incisor was subsequently moved toward the midline and reshaped with a composite buildup to serve as a new left central incisor. The combination of orthodontic, orthognathic and restorative treatment established a favourable occlusal and aesthetic result.